Retest reliability for complete airway interruption systems of aerodynamic measurement - Lamb, Jim R. (J Voice, 2020)
INTRODUCTION: Measures of subglottal pressure (Ps), phonation threshold pressure (PTP), and laryngeal resistance (LR) can be used as indicators of vocal cord disorders. The gold standard non-invasive measurement uses labial interruption, which has been shown to have reliability inconsistencies. Mechanical interruption methods have demonstrated promise in measurement reliability. The goal of the present study is to compare retest reliability of labial and mechanical interruption methods. METHODS: 55 subjects aged 18–69 participated. 10 trials were performed for each method. For labial interruption, subjects produced five labial plosives at comfortable and quiet volumes. For mechanical interruption, subjects produced a sustained /α/ while a balloon valve interrupted phonation five times. 30 subjects completed a second study visit identical to the first approximately two weeks (15 days ± 3.76) after the first visit. Ps, PTP, mean airflow rate (MFR), and LR were determined for each subject and retest reliability for each was analyzed. RESULTS: The percent difference in measurement results for test-retest of Ps were 12.88% ± 10.15 for mechanical interruption and 27.56% ± 17.14 for labial interruption (p = 0.0003). The percent difference for PTP measurements were 21.46% ± 16.01 for mechanical and 17.04% ± 14.62 (p = 0.3372) for labial. Intra-subject coefficients of variation of Ps were 0.086 ± 0.046 for mechanical and 0.161 ± 0.078 for labial (p < 0.0001). For PTP, the coefficients were 0.177 ± 0.083 for mechanical and 0.186 ± 0.091 for labial (p = 0.5402). Lastly, for LR (Ps divided by MFR) the percent differences were 14.33% ± 10.06 for mechanical and 53.87% ± 43.19 for labial (p < 0.0001) with intra-subject variability of 0.115 ± 0.050 for mechanical and 0.287 ± 0.222 for labial (p < 0.0001). CONCLUSIONS: Ps and LR measured using mechanical interruption showed more consistency for both retesting across separate study visits and intra-subject variability. PTP was similar in retesting and intra-subject variability. Continued work to improve mechanical interruption techniques is warranted as these methods offer higher reliability and consistency than the labial interruption methods.